ANALYTIC HIERARCHY PROCESS (AHP): SEBUAH METODE PEMBOBOTAN ALTERNATIF DALAM PEMBAGIAN DANA ALOKASI UMUM (DAU) Studi Kasus di Propinsi D.I. Yogyakarta - Bambang Kustituanto; Yansekardias Yansekardias (Journal of Indonesian Economy and Business (JIEB), 2001)
The title of this study is “Analytic Hierarchy Process (AHP): An Alternative  Weightiness Method for General Purposed Transfer (Dana Alokasi Umum, DAU) Distribution, a Case Study in D.I. Yogyakarta Province”. This research purposed to examines regional government perspective about the factors that influence DAU distribution in Indonesia. This research is used AHP method, which designed to examines the individual perspective, that will be concluded as a regional government perspective, closely related to the objectives that will be achieved. By using the individual perspective in decision making process, it can be answer the prominent weakness of decision making method that solely concern to the secondary data. The method can be the best alternative, while the quality of secondary data in developing countries occasionally incredible. In term of the suggested model, it is used to measure the weight of each variable in the model.According to regional government perspective in this study, we identified that the prominent consideration in DAU distribution is concentrated to fulfill the regional minimum requirement, then to support the financing of authority delegation, and the last to create fiscal equalization horizontally. By integrating the three aspects, we know weight or priority of variables used in DAU distribution as follows: regional revenue, poverty rate, gross domestic regional product (excluding oil and gas), population, area covered, and accessibility.